2011
DOI: 10.1002/iub.445
|View full text |Cite
|
Sign up to set email alerts
|

Defective resolution of pH2AX foci and enhanced DNA breakage in ionizing radiation‐treated cockayne syndrome B cells

Abstract: SummaryWe have previously shown that DNA repair of oxidized bases (either purines or pyrimidines) is inefficient in cells from patients with Cockayne syndrome (cs), a rare developmental and neurological genetic disorder. Here, we show for the first time that resolution of ionizing radiation (IR)-induced pH2AX foci, an indicator of DNA double-strand breaks, is significantly delayed in IR-treated cells belonging to the B complementation group of cs (csb). Using alkaline single-cell gel electrophoresis, which pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…We have found that Cav-1 expression increased with time in multiple PC cell lines after radiation, similar to a previous report13. After radiation, phosphorylated H2A.X is recruited to sites of double strand DNA breaks, and itself recruits proteins to effect DNA repair3839. We have extended our results to show that Cav-1 down-regulation leads to delayed repair of radiation-induced DNA damage, as demonstrated by delayed pH2A.X foci resolution.…”
Section: Discussionsupporting
confidence: 89%
“…We have found that Cav-1 expression increased with time in multiple PC cell lines after radiation, similar to a previous report13. After radiation, phosphorylated H2A.X is recruited to sites of double strand DNA breaks, and itself recruits proteins to effect DNA repair3839. We have extended our results to show that Cav-1 down-regulation leads to delayed repair of radiation-induced DNA damage, as demonstrated by delayed pH2A.X foci resolution.…”
Section: Discussionsupporting
confidence: 89%
“…The sensitivity of CSB-defective cells to oxidative DNA damage (10,11) indicates that CSB deficiency is phenotypically distinct from classic NER deficiencies and indicates that CSB function is not limited to monoadduct lesions. Therefore, transcription blockage by DSBs may also elicit CSB function to recruit repair factors most suitable for strand break repair at actively transcribed regions.…”
Section: Csb Function Is Necessary For the Recruitment Of Recombinatimentioning
confidence: 99%
“…As noted, in addition to UV sensitivity, CS patients also manifest severe neurodegeneration (8,9), suggesting the importance of CS proteins in maintaining genome stability against a broad spectrum of DNA damage. For example, CSB-defective cells are also sensitive to ionizing radiation (IR) (10,11), which is phenotypically distinctive from classic NER deficiencies and indicates that CSB function is not limited to UV-derived photo lesions. In addition, CSB-deficient mice exhibit a subset of symptoms found in patients, primarily UVC sensitivity and susceptibility to skin cancer (12).…”
mentioning
confidence: 99%